Komunikasi Antarpersona - Alqanitah Pohan (Universitas Islam Negeri Imam Bonjol Padang, 2013)
Man in life should be to communicate, it means other people need and require groups or communities to interact. This is a personal nature that most ofthe human form of social integration results with each other. In human life are of ten confronted each other in a container both formal and informal. Communication has a very important role in every day life. Communication is an important medium for the formation or personal development tfor social contact. Through communication a person growand learn, discover our personal and others, we hang out, friendly, hostile, love or love others, hate others and so on.